2018
DOI: 10.3390/ma11122403
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Cementite Precipitation during the Non-Isothermal Process by Applying Tensile Stress in GCr15 Bearing Steel

Abstract: In this work, the non-isothermal process of GCr15 bearing steel after quenching and tempering (QT) under different tensile stress (0, 20, 40 MPa) was investigated by kinetic analysis and microstructural observation. The Kissinger method and differential isoconversional method were employed to assess the kinetic parameters of the microstructural evolution during the non-isothermal process with and without applied stress. It is found that the activation energy of retained austenite decomposition slightly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Non-isothermal tests are mostly preferred for the dynamic analysis. To this end, many models, such as Kissinger, Flynn–Wall–Ozawa, Šatava–Šesták, and Friedman, were established to study the dynamic parameters of various materials based on the Arrhenius equation [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-isothermal tests are mostly preferred for the dynamic analysis. To this end, many models, such as Kissinger, Flynn–Wall–Ozawa, Šatava–Šesták, and Friedman, were established to study the dynamic parameters of various materials based on the Arrhenius equation [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional bearing steel 100Cr6 has high hardness and good wear resistance, but it has defects in toughness and temperature bearing capacity. In recent years, many scholars have done a lot of research on the microstructure evolution and manufacturing process optimization of 100Cr6 steel [6,7]. Yusuke et al [8] found that the quenched structure with almost no grain boundary carbides can be obtained by grain boundary amelioration (GBA) treatment, and the toughness can be increased to more than 5 times of the conventional one.…”
Section: Introductionmentioning
confidence: 99%
“…High-carbon chromium bearing steel probably is the most important material used for mechanical rolling components, which should have excellent surface hardness for wear and fatigue resistance as well as microstructural stability at extreme temperatures [6,7]. However, since high-carbon chromium bearing steel is a hypereutectoid steel, excessive secondary cementite will precipitate along the grain boundary to form network carbide during the process of cooling after rolling, thus increasing the brittleness of steel and reducing its fatigue life [8]. Generally speaking, to reduce the amount of network carbide including two ways: one is to control the precipitation of carbide in the cooling process and the other is to relieve the formed network carbide.…”
Section: Introductionmentioning
confidence: 99%